Aktivasi Manuskrip Sufistik dalam Ruang Publik Digital: Analisis Konten Ngariksa TV oleh Oman Fathurahman - Dania Dania; Muhamad Abror; Alifah Alifah (Manuskripta, 2025)
Digital platforms increasingly mediate the circulation of Islamic textual traditions. This article examines how Sufi manuscript-based knowledge is disseminated via Ngariksa TV, a YouTube channel curated by Oman Fathurrahman, and how these manuscripts are “activated” as public knowledge. Using qualitative content analysis of three specific episodes (42, 63, and 64), the study analyzes video recordings, narration, and textual cues. The research focuses on Sufi concepts, text-based pedagogy resembling the bandongan format, and strategies for spiritual-ethical internalization. Findings reveal that Ngariksa TV functions as “public philology,” reintroducing manuscripts as authoritative sources for contemporary moral reflection rather than mere archival artifacts. By interpreting works like Tanbīh al-Māshī and Zubdat al-Asrār, the channel frames spiritual dispositions as practical ethics. While YouTube expands access, it also reshapes the traditional teacher-disciple intimacy. This study bridges Digital Religion with Future Philology, explaining manuscript-centered pedagogical transformations in digital spaces. === Platform digital semakin memediasi sirkulasi tradisi teks Islam di ruang publik. Artikel ini menelaah diseminasi pengetahuan sufistik berbasis manuskrip melalui kanal YouTube Ngariksa TV yang dikurasi Oman Fathurrahman. Menggunakan analisis konten kualitatif terhadap Episode 42, 63, dan 64, penelitian ini mengkaji rekaman video, narasi lisan, dan penanda tekstual. Analisis difokuskan pada dimensi konsep tasawuf, pola transmisi teks menyerupai sistem bandongan, dan strategi internalisasi nilai spiritual-etis. Hasilnya menunjukkan Ngariksa TV beroperasi sebagai "filologi publik" yang mengaktifkan manuskrip sebagai sumber otoritatif untuk refleksi moral kontemporer, bukan sekadar artefak arsip. Melalui penafsiran Tanbīh al-Māshī dan Zubdat al-Asrār, nilai seperti ḥusn al-ẓann dan akhlāq dibingkai sebagai disposisi praktis. Meski memperluas akses, YouTube mengubah intensitas relasi pedagogis tradisional. Studi ini berkontribusi menjembatani Digital Religion dengan Future Philology dalam menjelaskan transformasi pedagogi berbasis manuskrip di ruang publik digital.